The effects of controlled environment and diets on broodstock maturation, spawning, spermatophore quality and juvenile production of penaeus merguiensis (de Man) - Olubunmi, Akinfolajimi (Fakulti Sains dan Teknologi, 2010)
Some aspects of the maturation and artificial propagation of Penaeus merguiensis were studied. The percentage of naturally matured shrimps that were transported to the hatchery and spawned was 83.33% while the percentage of hatchery matured shrimps that spawned were 66.66%, 50.00%, 50.00% and 33.33% for broodstocks fed with squids (Loligo sp.), polychaete (Diopatra sp.), Artemia biomass and pellets diets, respectively.